Soil organic carbon becomes newer under warming at a permafrost site on the Tibetan Plateau - Chang Ruiying; Liu Shuguang; Chen Leiyi; Li Na; Bing Haijian; Wang Tao; Chen Xiaopeng; Li Yang; Wang Genxu (Soil Biology and Biochemistry, 2021)
Permafrost areas are experiencing fast and dramatic changes under global warming. Increased primary production and stimulated microbial activity have been widely observed in warming permafrost. However, the fate of permafrost soil organic carbon (SOC) remains elusive, and the potential mechanisms underlying warmingmediated SOC formation and old C decomposition are poorly understood. Here, using in situ six-year manipulative warming experiments with two scenarios (+2.4 degrees C and +4.9 degrees C for lower and higher scenarios, respectively, above the ambient temperature) at a permafrost site in the Tibetan Plateau, we observed that soil C sink increased in the surface 5 cm layer under the two warming scenarios. SOC exhibited a linear increase with warming duration at rates of 6.8% and 6.4% annually in the silt & clay fractions and aggregates, respectively. Warming-induced accumulations of SOC in the aggregates and silt & clay fractions were contributed mainly by plant-derived C and minorly by microbial necromass. However, the increased input of new plant-derived C was accompanied with an increasing loss of old C via enhanced respiration under warming, likely due to the mobilization and degradation of C in the aggregates and silt & clay fractions. Our study provides field-based evidence of the enhanced SOC accumulation in the Tibetan permafrost regions under warming, and improves process-based understanding of warming-induced new plant-derived C that could replace the protected old C in the aggregates and silt & clay fractions.